Für den Lebensraum von morgen. 50 Jahre Ausbildung in Raumplanung an der ETH Zürich. - (:unkn) unknown (vdf Hochschulverl., 2015)
Die ETH Zürich kann auf 50 Jahre Ausbildung in Raumplanung zurückblicken. 1965 gab es an der ETH Zürich erste Fortbildungsangebote für Berufstätige im Bereich Raumplanung. 1967 wurde ein interdisziplinäres zweijähriges Nachdiplomstudium (NDS) Raumplanung eingeführt. Im Zuge der Bologna-Reform wurde es 2005 vom Master of Advanced Studies in Raumplanung (MAS RP) abgelöst. Darüber hinaus besteht die Möglichkeit, einzelne Lehrmodule im Rahmen eines CAS (Certificate of Advanced Studies) oder DAS (Diploma of Advanced Studies) zu belegen. Pioniere, Absolventen, Mitwirkende und Wegbegleiter der Raumplanungsausbildung an der ETH Zürich äußern sich zu bedeutenden Wegmarken und Herausforderungen der Raumplanungsausbildung an der ETH Zürich und darüber hinaus.

The governance structures in urban and regional development have undergone processes of transformation since the medieval period, resulting in them becoming increasingly decentralised, diversified, and centred about "middle-class values". An essential part was played by the initial concepts of land ownership and planned land use. These were then complemented by additional items from land taxation to the concepts that began to evolve during the 20th century, including diverse elements such as land economics and social responsibility. This volume concentrates on a diverse range of topics centering on the relationships between governance and the organization of entities within both urban and rural areas. The essays indicate that the development of systems of governance runs parallel to and reflects the indelible print humankind has made upon all forms of landscape. Over time various forms of governance evolved, but in the course of the last century they also became more accountable. Together this resulted in a continual process of evolving boundaries and territories, of political changes, and of the subsequent divisions between urban and rural areas as well as urban subdivisions. In addition to this complex mixture of land and spatial planning issues, we are faced today with rapidly changing demographic profiles across all of Europe - and not the least with the emerging awareness of how social responsibilities impact this issue.
Keywords: Raumplanung; Raumplaner; Berufsausbildung; Institutionengeschichte; Lehre; Studium